Anxiety of Caregivers in Telerehabilitation Sessions During Covid 19 - Aysha Saghir Mohammad, Saba Yaqoob, Atia Ur Rehman, Muhammad Azzam Khan, Jamshaid Haider Malik, Sehrish Bari, Ruhamah Yousaf, Muhammad Ahmed, Arslan Saleem Chugtai (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Pandemics affect people in a defeatist manner and become stressful for people with relatives which need specific forms of care and attention. The study was conducted to find out if anxiety prevails among caretakers during the Covid-19 Pandemic as according to the literature review caregivers experience burden and fears related to their care-recipients and telerehabilitation. Material and Methods: The study used cross sectional survey and quantitative research.50 care-givers participated in the research where they filled online questionnaires inspired and derived from care-giver burden scale and beck anxiety inventory. Anxiety was clearly evident as most of the care-givers agreed to have feelings of nervousness 19 (38%), feeling anxious 18 (36%), feeling distressed 22 (44%), complaints about emotional burden 23 (43%) and 23 (46%) constant immersion in duties towards care-recipients. Results: SPSS tables depict the analyzed results and their interpretation. The results show 36%of the care-givers agreed that they face anxiety when a situation gets out of control, 44% were distressed about not getting enough help from healthcare team and other family and friends, 55% are apprehensive about their present condition and 46% are emotionally challenged and constantly immersed in duties owing to their family members. Conclusions: Anxiety and depression as a result of caregiving burden is common among care-givers and needs to be addressed as soon as possible. This makes it essential that health professionals pay heed and attention to develop interventions for care-givers and provide them with pertinent knowledge. Keywords: anxiety, care burden, caregiver, covid 19, pandemic, telerehabilitation